K-means properties on six clustering benchmark datasets - Fränti, Pasi; Sieranoja, Sami (Applied intelligence (Dordrecht, Netherlands), 2018)
This paper has two contributions. First, we introduce a clustering basic benchmark. Second, we study the performance of k-means using this benchmark. Specifically, we measure how the performance depends on four factors: (1) overlap of clusters, (2) number of clusters, (3) dimensionality, and (4) unbalance of cluster sizes. The results show that overlap is critical, and that k-means starts to work effectively when the overlap reaches 4% level.